Instructor-led oral debriefing technique in clinical nursing simulation: integrative review - Juliana da Silva Garcia Nascimento; Fabiana Cristina Pires; João Pedro Resende Castro; Kleiton Gonçalves do Nascimento; Jordana Luiza Gouvêa de Oliveira; Maria Celia Barcellos Dalri (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze available scientific evidence in literature pertaining to the elements that make the instructor-led oral debriefing technique in clinical nursing simulation feasible. Methods: An Integrative literature review along the following information sources: PubMed®, Scopus, Web of Science, Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) [Latin American and Caribbean Health Sciences Literature], Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Educational Resources Information Centre (ERIC). Results: 284 studies were identified, and 5 composed the sample. Four elements constitute oral debriefing: characteristics of the instructor; discussion format, debriefing structure; and time frame. The main benefit was to develop cognitive and psychomotor skills; and the challenge was to establish training for instructors. The studies showed high methodological quality. Final Considerations: The scientific deepening as to the elements, benefits, and challenges of oral debriefing enables its execution and offers quality to the nursing process.